Growth Performance, Serum Biochemical Profile, Oxidative Status, and Fertility Traits in Male Japanese Quail Fed on Ginger (Zingiber officinale, Roscoe) Essential Oil - Tchoffo Herve; Kana Jean Raphaël; Ngoula Ferdinand; Folack Tiwa Laurine Vitrice; Adoum Gaye; Moussa Mahamat Outman; Ngouozeu Moyo Willy Marvel (Veterinary Medicine International)
This study was designed to evaluate the effect of ginger (Zingiber officinale, Rosc.) essential oil on growth performance, serum biochemical profile, oxidative stress, and histological structure of testes and fertility traits in Japanese quail (Coturnix coturnix japonica). 96 three-week-old male Japanese quail weighing between 120 and 130 g were randomly assigned to 4 dietary treatment groups in a completely randomized design. Each group was divided into 4 replicates of 6 quails. Quails in control group received orally 100 μl/kg bw of distilled water, while the three test groups received, respectively, by gastric intubation 50, 100, and 150 μl/kg bw of ginger essential oil. At 12 weeks old, twelve birds per treatment were randomly selected and fasted for 24 hours, weighed, and slaughtered to assess organ and biochemical parameters. At the same period, 4 mature male quails per treatment were chosen at random and individually housed in cages, each with four untreated females for fertility and hatchability traits. The main results revealed that growth characteristics were not markedly (P>0.05) affected by essential oil whatever the dose. The left testis weight increased significantly (P<0.05) with 100 and 150 μl/kg bw of essential oil compared to the control. The serum content in total cholesterol and triglycerides, the liver weight, the serum content in transaminases, and malondialdehyde decreased in treated quails. The serum content in total protein and globulin and the antioxidant enzymes activities increased in treated birds compared to the control. The histological changes in the testis were less visible in treated Japanese quails. At the doses of 100 and 150 μl/kg bw, this essential oil induced a significant increase (P<0.05) in fertility rate compared to the control. Under the conditions of this study, the ginger rhizomes essential oil can be used in poultry to reduce the lipid peroxidation in reproductive tissues and improve the fertility traits.